2019
DOI: 10.1186/s12978-019-0811-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential excess of vaginal examinations during the management of labor: frequency and associated factors in 13 Peruvian hospitals

Abstract: Background A high number of vaginal examinations (VEs) may lead to a higher risk of infections, as well as discomfort/dissatisfaction with intrapartum care. Objective To determine the frequency of potential excess of vaginal examinations (PEVE) during the management of labor and identify its associated factors, in Peruvian hospitals. Methods Secondary analysis of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Furthermore, since the existing studies [ 29 32 ] concur with the recommendations of the labor and delivery of the guideline proposed by this study with regard to the necessity of involving women in the care process, women’s awareness should be raised about care and intervention. In fact, they should be involved in clinical decision-making [ 29 ] so that parturient women can act freely [ 30 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, since the existing studies [ 29 32 ] concur with the recommendations of the labor and delivery of the guideline proposed by this study with regard to the necessity of involving women in the care process, women’s awareness should be raised about care and intervention. In fact, they should be involved in clinical decision-making [ 29 ] so that parturient women can act freely [ 30 ].…”
Section: Discussionsupporting
confidence: 53%
“…The panel of experts also had a consensus in this regard and stated that frequent vaginal examinations should be avoided without acquiring permissions or proper justification of the parturient women. Tanaka et al [ 32 ] concluded that the number of examinations were more than 40% (5 and more) and vaginal examinations were 1.5 times more at night than daytime [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A standard obstetrical practice is to examine a woman in active labor approximately every 2 to 4 hours; therefore, a cutoff of ≥5 obstetrical examinations is often used to indicate a high frequency of inspections. 36 , 37 , 38 , 39 Here, we assessed the relationship between frequent obstetrical examinations in labor and increased risk of severe perineal trauma and showed a positive trend toward increasing the risk of OASIs; however, our results were underpowered to draw solid conclusions. The study by Gluck et al 40 is, to the best of our knowledge, the only study to examine the association between OASIs and the frequency of obstetrical examinations on a cohort of 22,387 laboring women.…”
Section: Structured Discussionmentioning
confidence: 87%
“…Teaching technical skills during medical training can present many ethical and medico-legal issues (1) . Vaginal examination is a procedure used frequently during the management of labor, especially to assess its beginning and to evaluate its progress (2) .…”
Section: Introductionmentioning
confidence: 99%